A Survey of the genus Theretra Hubner, 1819 (Lepidoptera: Sphingidae) from Kodaikanal Hills (Western Ghats), Tamil Nadu, India - Mathew, Pratheesh; Sivasankaran, Kuppusamy; Anand, Sekar; Ignacimuthu, Savarimuthu (International Journal of Scientific Research in Biological Sciences, 2019)
Kodaikanal hill station with its natural beauty and climatic conditions have become a noteworthy tourist spot in South India over the years. The ideal environmental condition and rich floral diversity homes for diverse fauna in Kodaikanal. Sphingid diversity of Kodaikanal has not been reported in the past. Through this study, we report the diversity and study of the external and genital morphologies of the genus Theretra Hubner, 1819 from Kodaikanal hills for the first time. A total of seven species were reported during the study, namely Theretra alecto, T. clotho, T. gnoma, T. nessus, T. oldenlandiae, T. pallicosta and T. silhetensis. Images and genitalia of male and female adult specimens are illustrated for each species.